STUDIES AND RESEARCH REGARDING THE SERVICES OFFERED BY THE SIBIU COUNTY DIRECTORATE OF PERSONAL REGISTRATION OFFERED TO ORGANIZATIONS WITH OBJECTS OF ACTIVITY IN NONCONVENTIONAL TECHNOLOGIES - Constantin Dorin Olteanu; Mihail Aurel Titu; Iuliana Moisescu; Nicoleta Madalina Nita (Nonconventional Technologies Review, 2023)
The development of the local and regional economy of the city and county of Sibiu makes many of the existing industrial organizations in order to meet the current quality needs as well as for the permanent improvement of the efficiency and effectiveness of the products, to use more and more often in the technological process of processing, nonconventional technologies. The need for staff for these organizations is increasing the human resources in the area are exceeded thus, a large part of the employees come from the neighboring counties. This greatly increased flow of people increases the social need on the line of civil status and records of people. Through the services offered, the Sibiu County Directorate of Personal Records meets these service needs by trying to solve the situations that arise along the lines of personal records and civil status.